A study of existing use case extensions and experience: a systematic review. Issue 4 (1st October 2020) - Arogundade, Oluwasefunmi'Tale; Olotu, Samuel Ibukun; Abayomi-Alli, Olusola; Misra, Sanjay; Ikotun, Abiodun Motunrayo
Abstract : Use case has embedded potentials that enable the diversity in its adoption to addressing other issues in software engineering. This objective of this paper is to gathered and classified use case researches carried out over the years and defines the state-of-art. We identified and analysed 62 relevant articles with deep insights into six different initiatives. The publications included 29 journal articles, 18 conference articles, 3 reports, 5 book chapters, 5 workshops and 2 symposiums. This study deduced that as many as 15 different extensions are proposed from use case ranging from formal descriptions to subjective methodology. Use case has evolved from initial functional requirement elicitation to a more formal and extensive structure. There are fewer publications in cloud computing and use case-based systems. This study contributed to the use case body of knowledge by assessing the extended initiatives and giving an overview of the challenges that are not yet resolved.